The influence of dietary macronutrients on liver fat accumulation and metabolism - Parry, S; Hodson, L (BMJ Publishing Group, 2017)
The liver is a principal metabolic organ within the human body and has a major role in regulating carbohydrate, fat, and protein metabolism. With increasing rates of obesity, the prevalence of non-alcoholic fatty liver disease (NAFLD) is growing. It remains unclear why NAFLD, which is now defined as the hepatic manifestation of the metabolic syndrome, develops but lifestyle factors such as diet (i.e total calorie and specific nutrient intakes); appear to play a key role. Here we review the available studies, observational and intervention that have investigated the influence of diet on liver fat content. Findings from observational studies are conflicting with some reporting that relative to healthy controls, NAFLD patients consume diets higher in total fat/saturated fatty acids (SFA), whilst others find they consume diets higher in carbohydrates/sugars. From the limited number of intervention studies that have been undertaken, a consistent finding is a hypercaloric diet, regardless of whether the excess calories have been provided either as fat, sugar, or both, increases liver fat content. In contrast, a hypocaloric diet decreases liver fat content. Findings from both hyper- and hypo-caloric feeding studies provide some suggestion that nutrient composition may also play a role in regulating liver fat content and this is supported by data from isocaloric feeding studies; fatty acid composition and/or carbohydrate content/type appear to influence whether there is accrual of liver fat or not. The mechanisms by which specific nutrients, when part of an isocaloric diet, cause a change in liver fat remain to be fully elucidated.